2004
DOI: 10.1002/jtr.504
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific encounters, norms and crowding of summer visitors at alpine ski areas

Abstract: Operating chairlifts at alpine ski areas during the summer to accommodate tourism and recreation activities (e.g. hiking and mountain biking) is increasing in popularity. Increasing summer use, however, may affect the ability of ski areas to sustain acceptable social conditions (e.g. crowding). In addition, little is known about encounters, crowding or acceptable use levels at ski areas during the summer. This article addresses these issues using data from surveys of summer visitors (n = Keywords: crowding; en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 38 publications
3
39
1
2
Order By: Relevance
“…Pickering and Hill (2003) suggested that the increased popularity of both traditional resort-based tourism and expansion of the range of activities that has occurred within and near these Australian snowfields substantially increase both direct and indirect impacts on the biota, much of it endemic to the area. A reflection of concern for the impacts of expanded use of ski resorts is that tension has increasingly led to friction between developers and conservationists (Needham et al 2004). …”
Section: Mountain Bikingmentioning
confidence: 99%
“…Pickering and Hill (2003) suggested that the increased popularity of both traditional resort-based tourism and expansion of the range of activities that has occurred within and near these Australian snowfields substantially increase both direct and indirect impacts on the biota, much of it endemic to the area. A reflection of concern for the impacts of expanded use of ski resorts is that tension has increasingly led to friction between developers and conservationists (Needham et al 2004). …”
Section: Mountain Bikingmentioning
confidence: 99%
“…In a parallel study on place satisfaction, Eder and Arnberger [36] posits that place attachment determines a higher level of attachment to an area for a particular activity preferred by the individual. Crowding due to level of activities/norm of behaviour was found to be reliant on site-specific encounters leading to less acceptable crowding for various activities and locations [22,37]. Activities enjoyed at a forest retreat highlighted that there was little difference between activities enjoyed by different ethnic groups [38].…”
Section: Activitiesmentioning
confidence: 99%
“…In comparison, more rigorous methodologies for visitor monitoring are common in other fields of outdoor recreation and tourism. For example, periodic surveys are used to determine acceptable crowding norms for trail walking (Arnberger & Haider, 2007) and summer hiking (Needham, Rollins, & Wood, 2004), while the efficacy of automatic counter and visual recording technologies in parks has been established for some time (Cessford & Muhar, 2003 (Orellana, Bregt, Ligtenberg, & Wachowicz, 2012;Taczanowska, Muhar, & Brandenburg, 2008;D'Antonio et al, 2010;Leung, Walden-Schriener, & Miller, 2012).…”
Section: Ski Resort Managementmentioning
confidence: 99%